Prevalence of and factors associated with acute diarrhea among children under five in rural areas in Ethiopia with and without implementation of community-led total sanitation and hygiene - Gezahegn Mernie; Helmut Kloos; Metadel Adane (BMC, 2022)
Abstract Background Since Ethiopia has been implemented the Community-Led Total Sanitation and Hygiene (CLTSH) approach to control incidence of diarrhea, few studies have compared the prevalence of diarrhea and associated factors in rural areas that have implemented this approach with those that have not implemented it, and none have examined it in the district of Menz Gera Midir in the Amhara Region of Ethiopia. This study addressed this gap. Method A community-based comparative cross-sectional study was conducted among 224 children under five in three randomly selected rural kebeles (the smallest administrative units in Ethiopia) where CLTSH had been implemented and 448 similar children in three other randomly selected rural kebeles where CLTSH had not been implemented during February and March, 2020. Data were collected using a structured questionnaire and an on-the-spot observational checklist. Data were analyzed using three different binary logistic regression models with 95% confidence interval (CI): the first model (Model I) was used for CLTSH-implementing kebeles, the second model (Model II) for non-CLTSH-implementing kebeles, and the third model (Model III) for pooled analysis of CLTSH-implementing and non-implementing kebeles. To control confounders, each multivariable logistic regression model was built by retained variables with p < 0.25 from the bi-variable logistic regression analysis. From the adjusted multivariable analysis of each model, variables with p-values < 0.05 were declared factors significantly associated with acute diarrhea. Results The prevalence of acute diarrhea among children under five from households in kebeles that had implemented CLTSH was 10.6% (95% CI:6.6-14.7%) and among those that had not implemented CLTSH 18.3% (95%CI:14.8-22.2%). In CLTSH-implementing areas, use of only water to wash hands (AOR: 3.28; 95% CI:1.13-9.58) and having a mother/caregiver who did not wash their hands at critical times (AOR: 3.02; 95% CI:1.12-8.12) were factors significantly associated with acute diarrhea. In non-CLTSH-implementing areas, unimproved water source (adjusted odds ratio [AOR]: 2.81; 95% CI:1.65-4.78), unsafe disposal of child feces (AOR: 2.10; 95% CI:1.13-3.89), improper solid waste disposal (AOR: 1.95; 95% CI:1.12-3.38), and untreated drinking water (AOR: 2.33; 95% CI:1.21-4.49) were factors significantly associated with acute diarrhea. From the pooled analysis, not washing hands at critical times (AOR: 2.54; 95% CI:1.59-4.06), unsafe disposal of child feces (AOR: 2.20; 95% CI:1.34-3.60) and unimproved water source (AOR: 2.56; 95% CI:1.62-4.05) were factors significantly associated with the occurrence of acute diarrhea while implementation of CLTSH was a preventive factor (AOR: 0.24; 95%: 0.20-0.60) for the occurrence of acute diarrhea. Conclusion The prevalence of acute diarrhea among under-five children in Menz Gera Midir District was lower in kebeles where CLTSH had been implemented than in kebeles where CLTSH had not been implemented. Therefore, we recommend that governmental and non-governmental sectors increase implementation of CLTSH programs, including improving handwashing at critical times, promoting safe disposal of child feces and enhancing the availability of improved water sources.